PENGARUH IKLAN DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN STUDI KASUS PADA CV CEMILAN KUNIK GARUT - Hari Mulia (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2020)
The purpose of this study was to determine the advertising, product quality and purchase decisions at CV Cemilan Kunik Garut and to determine the effect of advertising on purchasing decisions, the effect of product quality on purchasing decisions, and the effect of advertising and product quality on purchasing decisions on food products CV Cemilan Kunik. Arrowroot. The research method used is descriptive method. Descriptive method is a research conducted to determine the value of the independent variable, either one or more (independent) variables without making comparisons, or connecting one variable to another. The population in this study were all consumers who had purchased products in CV Cemilan Kunik Garut food products, while the samples taken were 68 people and the sampling was carried out using incidental sampling. Based on data processing using SPSS veri 20, the research instrument used in this study was declared valid because it had a value greater than the r table of 0.238 and reliable because it had a value greater than the Cronbach alpha value of 0.600. From the results of the correlation test, advertising has a strong influence on purchasing decisions with an r value of 0.646 and a determination coefficient of 41.3% and the remaining 58.7% is influenced by other factors not examined, while the results of the product quality correlation test have a strong influence on purchasing decisions. r value of 0.634 and coefficient of determination of 43.3% and the remaining 56.7% influenced by other factors not examined. Then the results of the advertising correlation test and product quality have a very strong influence on purchasing decisions with an r value of 0.824 and a determination coefficient of 67.9% and the remaining 32.1% is influenced by other factors not examined.